A Novel Variant Of Regenerating Iα Gene (REG) In Type II Diabetics Among Pakistani Targeted Population - Sadaf Saleem; Saeeda Baig; Sadia Farrukh; Mazhar Shafiq (Journal of Rawalpindi Medical College)
Objective: Regeneration of pancreatic β-cells, is an essential step towards diabetes management. The regenerating (REG) Iα gene is secreted from damaged β-cell for the synthesis of β-cell. This study aimed to identify REG Iα gene polymorphisms and their association with Type II diabetes (T2DM).